Basal and reactivity levels of cortisol in one-month-old infants born to overweight or obese mothers from an ethnically and racially diverse, low-income community sample. (February 2018) - Jones-Mason, Karen M.; Coccia, Michael; Grover, Stephanie; Epel, Elissa S.; Bush, Nicole R.
Highlights: Infant basal cortisol and reactivity were measured in a low SES/high risk sample. Infant basal cortisol and reactivity were lower than in reviews of low-risk samples. Infant variability in cortisol levels suggests diversity in cortisol outcomes. Abstract: Establishing typical values of the steroid hormone cortisol at rest and after challenge is critical for understanding how environmental factors impact stress regulation and overall development, beginning at birth. Yet most extant samples are small or based upon low-risk populations, and few studies address the potential role of maternal weight during pregnancy in their study designs or sampling strategy. Here we report basal and reactivity levels of salivary cortisol within a racially and ethnically diverse sample of 132 infants approximately one month of age (Age in days: M = 37.61, SD = 7.27) born to lower income overweight or obese mothers. Reactivity was assessed in response to a multi-domain infant stressor paradigm, which included assessment via the Newborn Behavioral Observation (NBO) system and extensive anthropometric measurements. Sample means for basal, post stressors, and reactivity to the NBO were significantly lower than those reported in reviews of low-risk samples. Parity was associated with cortisol levels such that first-born infants had lower resting cortisol and higher reactivity than infants born to multiparous women. Latino infants had lower basal cortisol. No other demographic characteristics significantly predicted cortisol. The variability in cortisol levels present in this sample suggests that considerable psychophysiological diversity may exist in samples of low-SES or high-risk participants. Findings provide useful ranges for samples of racially and ethnically diverse newborns from low-income families.